2022
DOI: 10.1001/jamanetworkopen.2021.45870
|View full text |Cite|
|
Sign up to set email alerts
|

Reasons for Suicide During the COVID-19 Pandemic in Japan

Abstract: IMPORTANCEAlthough the suicide rate in Japan increased during the COVID-19 pandemic, the reasons for suicide have yet to be comprehensively investigated. OBJECTIVE To assess which reasons for suicide had rates that exceeded the expected number of suicide deaths for that reason during the COVID-19 pandemic. DESIGN, SETTING, AND PARTICIPANTS This national, population-based cross-sectional study of data on suicides gathered by the Ministry of Health, Labor, and Welfare from January 2020 to May 2021 used a times-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 56 publications
(112 reference statements)
2
62
0
1
Order By: Relevance
“…examined monthly trends in suicide rates by reason up to May 2021. 24 The results showed that Japanese women experienced an increase in suicide in all reason categories during the pandemic, and in particular, an increase in suicides for reasons related to family, health and work. Ando et al.…”
Section: Discussionmentioning
confidence: 96%
“…examined monthly trends in suicide rates by reason up to May 2021. 24 The results showed that Japanese women experienced an increase in suicide in all reason categories during the pandemic, and in particular, an increase in suicides for reasons related to family, health and work. Ando et al.…”
Section: Discussionmentioning
confidence: 96%
“… 2 , 3 To illustrate, the increasing prevalence of major depressive and anxiety disorders in 2020 was positively related to the degree of pandemic seriousness in 204 countries 5 ; however, contrary to expectations, most studies from numerous countries reported that suicide mortality in 2020 did not increase, with the exceptions of Japan, India, Puerto Rico and Vienna (in Austria). 6 , 7 , 8 , 9 , 10 , 11 , 12 13 …”
Section: Introductionmentioning
confidence: 99%
“… 13 During the first wave of the pandemic (between March and June 2020), suicides decreased, 12 , 13 whereas, during the second half of 2020, they increased with the highest excess in October 2020 (in females more than males). 11 13 Copycat suicide 15 was considered to play important roles in the drastic/transient increasing female suicides in October 2020 11 ; however, the drastic/transient increasing suicides observed in the second half of 2020, diminished thereafter but increasing trends persisted during the first half of 2021. 13 Considering these findings, the mechanisms of increased suicides in Japan during the pandemic may have involved complex factors, such as region, gender, age, and pandemic duration.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Thus, suicide among youth has become a topic of concern as the pandemic continues to affect the general population, 3 especially in Japan, where suicide has been the number one cause of death for young populations. 4 Studies have extensively investigated the trends in suicide during the pandemic among the general population in Japan 5 , 6 , 7 , 8 and abroad, 9 , 10 which found that suicide rates initially decreased compared to previous years 5 but subsequently increased into 2021. Of note, two studies provided robust evidence that suicide rates among younger populations in Japan increased later into the pandemic in 2020, after accounting for time trends and seasonality.…”
Section: Introductionmentioning
confidence: 99%